IMPROVING STUDENTS’ WRITING SKILL ON RECOUNT TEX THROUGH DIARY WRITING AT EIGHTH GRADE OF MTS PONDOK PESANTREN ULUMUL QUR’AN MEDAN - Siregar, Kaaf Iklilah (BRIGHT VISION Journal of Language and Education, 2021)
This research was aimed at implementing diary writing as a medium to improve the writing skills of the eighth grade of MTs Pondok Pesantren Ulumul Qur’an Medan in the academic year of 2020/2021. This research was an action research study. The participants of this research were 22 students of grade VIII, the English teacher, and the collaborator. This research used two types of data, namely qualitative data and quantitative data. The qualitative data were obtained through an interview with the English teacher and the students and observations during the teaching and learning process. Meanwhile, the quantitative data were in the form of the results of the students’ writing before the implementation of the actions (pre-test) and after the implementation of the actions (post-test). The results of the research showed that there were improvements on the students’ writing skills. The research uses two cycles, each cycle consist of planning, action, observation, and reflection. The result of this research shows that there is an improvement of the students’ writing skills in recount text. It can be seen from t-test calculation in cycle I shows that the score of pre-test 35.9 and the score of post-test is 57.72. Meanwhile, the cycle II shows that the score of pre-test is 57.72 and score of post-test is 83.86. This indicates that by applying of diary writing can improve the writing skills of the second grade students of MTs Pondok Pesantren Ulumul Qur’an Medan is accepted. Keywords: Diary Writing, Improve, Writing, Writing Skills, Recount Text.